PENGARUH BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KECERDASAN SPIRITUAL SISWA KELAS X SMA NEGERI 2 PEKANBARU TAHUN PELAJARAN 2014/2015 - Sri Mawarni; Rosmawati '; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the level of spiritual intelligence of students before and after the given group counseling and guidance to know how much influence the group to increase spiritual intelligence of students in class X SMA Negeri 2 Pekanbaru school year 2014/2015. Question in this study is: How much influence the group guidance to increase students' spiritual intelligence? Method in this study is a quasi experimental study with pretest-posttest design. Population of this study amounted to 76 students. Sampling technique is purposive sampling. Samples were taken from 25% of the population, so that elected 30 students who have low spiritual intelligence in class X SMA Negeri 2 Pekanbaru. Results of this research study shows that there are significant positive effect of group counseling to increasing the spiritual intelligence class X SMA Negeri 2 Pekanbaru by 25%. To further research in order to conduct research on spiritual intelligence with different variables, such as Effect of Group Counseling Service Improvement Spiritual Intelligence Students Against IsolatedKeywords: Guidance Group, Spiritual Intelligence